Legal representation and a Bill of Rights - Lawrenson, Natalie Carina (2021)
The right to legal representation has been acknowledged as a fundamental right of an accused in a criminal trial. 1 Traditionally, however, this, right has been viewed as a right to retain counsel, rather than a positive right to be provided with legal representation in the case of indigent accused. The importance of legal assistance for accused persons being tried in an adversarial justice system has been recognised in the Anglo-American legal systems. In an adversarial system the duty of a presiding officer is to act as an independent and objective adjudicator of the facts and evidence presented to him or her by the two parties to the trial. The onus is on the litigants to advance their own case. It naturally follows that the strength of a party's case depends on the skill of the litigator